Pengayaan biskuit dengan fortifikasi fraksi tidak tersabunkan mengandung senyawa bioaktif multi komponen dari distilat asam lemak minyak sawit - Kgs Ahmadi; Teti Estiasih; Wahyu Erwin Firmansyah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Palm Fatty Acid Distillate (PFAD) is a by product of CPO (crude palm oil) physical refining. PFAD containing multicomponent bioactive compounds such as tocopherols, tocotrienols, phytosterols, and squalene which accumulated in unsaponifiable fraction (UF) and can be separated by saponification. Utilization of bioactive compounds can be applied on food products by fortification into biscuits. The research aimed to determine the effect of addition level of UF from PFAD on physical and organoleptics of the biscuits and also to determine chemical characteristic and bioactive compounds from the best treatment biscuit. The method used a completely randomized design with one factor, namely the level of addition of the UF from PFAD consisted of 6 treatments and was repeated four times. Data were analyzed using Analysis of Variance (ANOVA), then continued using the Duncan’s Multiple Range Test (DMRT) with significance level of 5%. The best treatment in this study was a treatment which contained 0.5% (w/w) of the UF from PFAD. The best biscuit had chemichal characteristics included those were the water content 1.81 ± 0.06%, 2.10 ± 0.06% ash content, 27.98 ± 0.54% fat content, 8.04 ± 0.13% protein content, 0.22 ± 0.02% crude fiber content, 60.07 ± 0.66% carbohydrate content, 2.66 ± 0.00002% FFA, and 7.10 ± 0.19 mek/kg total oxidation. The best biscuit contained bioactive compounds such as 147.19 ppm α–tocotrienol, 190.30 ppm δ–tocotrienol, 68.091 ppm ϒ–tocotrienol, 5,848.45 ppm β–sitosterol, 143.97 ppm stigmasterol, 621.09 ppm campesterol, and squalene content 3,284.50 ppm.